Selection of Acehnese germplasm of rice (Oryza sativa L.) using SRI approach in the post-tsunami affected area of Aceh Province, Indonesia - . Efendi; Elly Kesumawati; . Bakhtiar; Sabaruddin Zakaria (Syiah Kuala University, 2012)
After affected by the giant tsunami waves following the 9.1 earthquake on December 26, 2004 in Aceh province of Indonesia, many of natural resources were damaged, including the loss of germplasm of rice in low land area. Therefore, we attempt to collect and evaluate the Acehnese germplasm of rice. We identified the Acehnese accession of rice by describing the characteristics of the rice plant using cultivation method of system for rice intensification or SRI with organic approach. Some of the descriptors include days of tillage formation, days from emergence to flowering, kernel weight, plant height, and yield components. We found that the Acehnese rice germplasm collection is very diverse: the days of tillage formation is 6 to 18 days after planting; the days from emergence to flowering is 56 to 90 days, plant height is 77 to 121 cm, and 1,000 kernel weight is 19.47 to 30.27 g. So, we concluded that the diversity of Acehnese rice is very rich, the rice accessions were identified and now stored in the cool storage system. Evaluation of the accession showed considerable promise as material research with high yield potential, high levels of tolerance to stresses such as weeds, drought, acidity and blast for further evaluation. The progenies might provide the improved sustainability of intensified systems through durable crop resistance to biotic and abiotic stress. In the future, characterization traits will be selected for resistance to pests-diseases, and tolerance to drought and salinity stresses, as well as analysis of grain quality. We will also develop the high multiple resistance to environmental stresses.